توزيع الزكاة في الهيئة الوطنية للزكاة في إندونيسيا: دراسة فقهية تقويمية = Zakah distribution in the National Zakah Board of Indonesia: a juristic evaluative study - Hambari, Hambari; Arif, Arif Ali; Zaim, Muntaha Artalim (IIUM Press, 2021)
This research aims to analyse the experience of the National Zakah Board in Indonesia (BAZNAS) in the management of zakah and the jurisprudential evaluation of the distribution process. The paper selects BAZNAS for analysis as this institution is the national zakah management coordinator and has applied modern zakah management system that became reference for other zakah institutions in the province, city, and regency levels. This research uses three methods including inductive and analytical approaches and field study to achieve its objectives. Some important findings of this research are: this organization strictly distributes zakah to eight zakah recipients as mentioned in the Quran, 9: 60, including the poor, the needy, those employed to collect it, to attract the hearts of those who have been inclined towards Islam, to free the slaves, for the debtors, for the sake of Allah and the stranded travellers; the definition of each of these categories (used in this organization) is in accordance with the concept of contemporary jurisprudence and also based on the country’s circumstances; the research shows that the zakah distribution applied in BAZNAS has two different methods including direct and indirect approaches; it is also found that there are two types of distribution programmes, i. e. consumption-based and production-based programmes. These are in accordance with Shariah and its objectives.